Optimization in the production of marine microalgae Nannochloropsis oculata in a helical tubular photobioreactor - Carvajal-Oses, María del Milagro (2018)
Microalgae production has become important in recent years due to its diverse uses in the industry (biofuels, human and animal feeding, and bioremediation), because is important the optimization of the technologies destined to its production is necessary. A tubular photobioreactor with a traditional open system for production of Nannochloropsis oculata in the Parque Marino del Pacífico, Puntarenas, Costa Rica, was compared. In the construction of the photobioreactor was used 100 meters of transparent hose 1 “with a total volume of 55 L, a cylindrical structure (diameter 0, 67 m and 1, 90 m height), a manifold (0, 12 m diameter and 1, 25 m height) of 15 L of volume, a degasser to remove excess oxygen, an aerator was installed for the corresponding mixing of the culture medium and finally eight lamps of 32 W were placed around the metallic structure. While the open system consisted of glass fiber tanks 2 m3 and a hose for aeration. Results showed with tubular photobioreactor it was possible to increase the algal density from 7,5 to 134 x 106 cells / mL, the microalga managed to remain in the system for up to 20 days while with the common open system only 4 to 5 days, the new equipment reduced the area required for microalgae production by 91% and by reducing the man hours required for its operation managed to reduce economic costs by 18%.